A fully validated microbiological assay to evaluate the potency of ceftriaxone sodium - Maria Luisa Manfio; Danielle Araújo Agarrayua; Jaison Carlosso Machado; Cleber Alberto Schmidt (Universidade de São Paulo, 2013)
Ceftriaxone (CFTX) sodium is a third-generation, broad-spectrum cephalosporin that is resistant to beta-lactamases. An alternative bioassay for the assessment of the potency of this drug in pharmaceutical formulations has not been previously reported. Thus, this paper reports the development and full validation of a 3 x 3 agar diffusion bioassay using a cylinder-plate method to quantify CFTX sodium in pharmaceutical samples. The strain Staphylococcus aureus ATCC 6538P was used as the test microorganism, and the results of the proposed bioassay displayed high linearity, precision, accuracy, specificity and robustness. All potency results were statistically analyzed using an analysis of variance (ANOVA) and were found to be linear (r=0.99999) in the range of 16-64 µg/mL, accurate (100.5%), and precise [repeatability: relative standard deviation (RSD)=1.4%; intermediate precision: between-day RSD=2.1% and between-analyst RSD=2.5%]. The specificity of the bioassay was determined by evaluating a degraded sample (50 ºC) at 0, 24 and 48 hours as compared against the results from the pharmacopeial liquid chromatography method for CFTX. The results validated the proposed microbiological assay, which allows reliable quantitation of CFTX in pharmaceutical samples. Moreover, it is a useful, simple and low-cost alternative method for monitoring the quality of this medicine.